Availing health services—A study on social barriers and perceptions among women of reproductive age group in Bankura District, West Bengal, India - Roy, Samraggi; Thomas, Ebbie; Govindaraj, Mahalingam; Nair, Sirimavo (Frontiers in Nutrition, 2025)
Despite advancements in health and technology, anemia continues to be a significant health concern for pregnant and lactating women in low- and middle-income countries, contributing to both morbidity and mortality. This study aims to explore the behavioral aspects and societal influences that affect adherence to health services and the adoption of healthy nutritional habits among women of reproductive age. Focus group discussions (FGDs) were conducted among Pregnant women, lactating mothers, and their respective mothers-in-law in four Gram Panchayats of Bankura District, West Bengal, India. The qualitative data from six focus group discussions (FGDs) were analyzed using thematic analysis in NVivo version 14.23.3. To develop thematic elements relevant to program objectives, a process of inductive coding was undertaken to support coding and creation of major themes. In addition, theme and code coverage visualizations assisted in identifying barriers, along with participant quotes and excerpts noted verbatim. The study identifies key barriers to compliance with anemia control programs, including inadequate consumption of iron and folic acid-rich foods, dislike for Iron and Folic Acid (IFA) tablets, forgetfulness, and limited awareness of anemia. Service gaps such as insufficient counseling on anemia, inadequate supply of IFA tablets, and health infrastructure issues exacerbate the problem. The focus group discussions revealed the behavioral and societal influence affects lack of adherence to services. These women portray lack of compliance with IFA tablets due to their dislike of the taste of the tablets and forgetting to take them due to increased household work, along with their aversion towards green-leafy vegetables. Additionally, these women claimed that there is an inadequate supply of IFA tablets for many lactating mothers as well as women in the reproductive age group (15–49 years of age). Gender disparities further compound these challenges, with unequal distribution of household labor and limited access to education for women contributing to nutritional deficiencies. Addressing these multifaceted issues requires comprehensive interventions focusing on nutrition education, healthcare access, and gender equality to effectively combat anemia among vulnerable populations.